2014
DOI: 10.11138/ads/2014.5.2.069
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of a new pulp capping cement

Abstract: SummaryAim. The aim of the present study was to evaluate the biocompatibility of a new pulp capping material (Biodentine, Septodont) compared with reference pulp capping materials: Dycal (Dentsply), ProRoot MTA (Dentsply) and MTA-Angelus (Angelus) by using murine odontoblast cell line and Alamar blue and MTT cytotoxicity tests. Methods. The citocompatibility of murine odontoblasts cells (MDPC-23) were evaluated at different times using a 24 Transwell culture plate by Alamar blue test and MTT assay. Results. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 39 publications
2
29
0
4
Order By: Relevance
“…Studies comparing the cell viability of Biodentine and MTA have shown the similarity between the 2 materials (23)(24)(25)(26)(27). Those results are in agreement with the findings of this study, which showed that Biodentine and MTA had a similar effect on cell viability.…”
Section: Discussionsupporting
confidence: 92%
“…Studies comparing the cell viability of Biodentine and MTA have shown the similarity between the 2 materials (23)(24)(25)(26)(27). Those results are in agreement with the findings of this study, which showed that Biodentine and MTA had a similar effect on cell viability.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with the early report of Poggio et al who described lack of cytotoxicity in MTA and biodentine 37) . Interestingly, MTA-BisBAL NPs seems to attract to HGF in comparison with MTA alone may be due to lipophilicity of BisBAL nanoparticles.…”
Section: Discussionsupporting
confidence: 93%
“…Once internalized, nanomaterials may cause a broad range of biological effects such as inflammatory responses, oxidative stress, DNA damage and apoptosis (Huang et al, 2013;Kodali et al, 2013;Sahu et al, 2013;Song et al, 2009;Stebounova et al, 2011;Steuer et al, 2014;Stoccoro et al, 2013;Ucciferri et al, 2014). Silica nanoparticles, for instance, have been shown to induce reactive oxygen species autophagy in human hepatocytes (Mohammadi et al, 2014;Poggio et al, 2014), neurotoxicity and Alzheimer-like pathology in human and mouse neuronal cells (Yang et al, 2014), spermatogenesis damage (Xu et al, 2014) and impairment of vascular homeostasis (Nemmar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%